2022
DOI: 10.3390/ijerph191911853
|View full text |Cite
|
Sign up to set email alerts
|

How Internet Websites Portray Herbal Vitality Products Containing Eurycoma longifolia Jack: An Evaluation of the Quality and Risks of Online Information

Abstract: Background: Tongkat Ali (TA) or Eurycoma longifolia is a herbal medicine (HM) plant traditionally used to treat sexual dysfunction and enhance libido in men. Websites containing information about HM are abundant. However, studies have shown that in general the quality of websites containing information on HM is low. The present study aims to assess the quality and risks of websites containing information about TA supplements and to identify the health claims for TA. Methodology: A cross-sectional study to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several tools have been developed to determine the content quality of web-based information, such as DISCERN, Journal of American Medical Association (JAMA) benchmark criteria, and Global Quality Score (GQS). To this point, some studies are notable regarding the evaluation of the quality and reliability of shared knowledge in the various websites [ 31 , 32 , 33 , 34 ]. For instance, Ng et al investigated the quality of online dietary and herbal supplement websites ( n = 87), according to the DISCERN instrument, and they found high variability in the DISCERN instrument scores across websites [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tools have been developed to determine the content quality of web-based information, such as DISCERN, Journal of American Medical Association (JAMA) benchmark criteria, and Global Quality Score (GQS). To this point, some studies are notable regarding the evaluation of the quality and reliability of shared knowledge in the various websites [ 31 , 32 , 33 , 34 ]. For instance, Ng et al investigated the quality of online dietary and herbal supplement websites ( n = 87), according to the DISCERN instrument, and they found high variability in the DISCERN instrument scores across websites [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the information about Ephedra sinica on online websites ( n = 28) had a poor quality [ 33 ]. Similarly, Wahab et al demonstrated, on the basis of a modified DISCERN tool, that websites ( n = 321) containing information about Eurycoma longifolia , which is an herbal medicine, were generally low-quality [ 34 ]. These studies show that there may be lower quality and reliability in online sources about dietary supplements with commercial value.…”
Section: Introductionmentioning
confidence: 99%